2017
DOI: 10.1007/978-3-319-66715-7_10
|View full text |Cite
|
Sign up to set email alerts
|

e2-Mask: Design and Implementation of a Mask-Type Display to Support Face-to-Face Communication

Abstract: In Face-to-Face communication, his or her face is an important part that decides the impression of a person because a person estimates the personality of the interlocutor from the features of the face of the interlocutor. Therefore, we made a hypothesis own impression and personality of giving to others by changing the own face freely. Then we proposed the e2-Mask that a mask-type display that synchronizes with facial expressions and substitutes an avatar for a human face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Utilising electrochromic (EC) display technology we were able to design and construct smart face masks that present a believable step towards a productizable solution. Whilst we did not explore mechanisms to control the display switching we believe that straightforward solutions can be found based on simplified versions of prior work on the topic [7,18]. Our approach of evaluating the face masks over a video conversation was mandated by the social isolation rules in operation at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilising electrochromic (EC) display technology we were able to design and construct smart face masks that present a believable step towards a productizable solution. Whilst we did not explore mechanisms to control the display switching we believe that straightforward solutions can be found based on simplified versions of prior work on the topic [7,18]. Our approach of evaluating the face masks over a video conversation was mandated by the social isolation rules in operation at the time of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on face masks covering the mouth, Kumazaki et al [7] developed a face mask display that tracks the wearer's facial expression and presents a photo realistic representation on the outward facing display Focusing to sensing the facial expressions of the wearer, Umezawa et al [18] developed the e2-Mask, that utilized 40 photo reflective sensors on the face to recreate facial expressions in an avatar. To support telepresence, Misawa and Rekimoto [11] demonstrated the ChameleonMask that displays a remote user's face on the face of a human-surrogate, and concluded that the surrogate is regarded as the actual (remote) person.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously explored a camera-based digital mask display, e2-Mask [37], which used two flat tablet displays and two webcameras to capture and reflect the face of the wearer on an avatar (Figure 3). Both displays and cameras are mounted on each side of the mask device, i.e.…”
Section: Camera-based Digital Mask Displaymentioning
confidence: 99%
“…To evaluate the feasibility of a digital face mask display based on photo-reflector sensor arrays (e2-MaskZ), we conducted user experiments to compare the sense of self-agency and self-ownership [9] toward the controlled avatar, between our mask and the camera-based digital face mask display (e2-Mask) [37].…”
Section: The Sense Of Self-agency and Self-ownershipmentioning
confidence: 99%